Factors affecting driving performance in patients with Multiple Sclerosis – still an open question - Seddiq Zai, Susan; das Nair, Roshan; Heesen, Christoph; Buhmann, Carsten; Pedersen, Anya; Pöttgen, Jana (Frontiers in Neurology, 2024)
Background and objectives Research on driving ability in people with multiple sclerosis (MS) suggests that they might be at risk for unsafe driving due to MS-related motor, visual, and cognitive impairment. Our first aim was to investigate differences in driving ability and performance between people with MS (PwMS) and those without any neurologic or psychiatric disease (“controls”). Secondly, we determined disease-related factors influencing driving ability in PwMS. Methods We prospectively compared standardized performance in a driving simulator between 97 persons with early MS [mean (SD) = 6.4 (7.3) years since diagnosis, mean (SD) Expanded Disability Status Scale (EDSS) = 2.5 (1.4)] and 94 group-matched controls. Participants completed an extensive examination comprising questionnaires and assessments regarding driving, cognitive and psychological factors, as well as demographic and disease-related measures. Between-group comparisons of driving-relevant neuropsychological tests and driving performance were done. Correlations were performed to define demographic and disease-related factors on driving performance in MS. Results In a driving simulator setting, PwMS had more driving accidents [T(188) = 2.762, p = 0.006], reacted slower to hazardous events [T(188) = 2.561, p = 0.011], made more driving errors [T(188) = 2.883, p = 0.004] and had a worse Driving Safety Score (DSS) [T(188) = 3.058, p = 0.003] than controls. The only disease-related measure to be associated with most driving outcomes was the Wechsler Block-Tapping test (WMS-R) backward: number of accidents (r = 0.28, p = 0.01), number of driving errors (r = 0.23, p = 0.05) and DSS (r = −0.23, p = 0.05). Conclusion Driving performance in a simulator seems to be reduced in PwMS at an early stage of disease compared to controls, as a result of increased erroneous driving, reduced reaction time and higher accident rate. MS-related impairment in mobility, vision, cognition, and in psychological and demographic aspects showed no or only minimal association to driving ability, but impairment in different areas of cognition such as spatial short-term memory, working memory and selective attention correlated with the number of accidents, and might indicate a higher risk for driving errors and worse performance. These results show that driving ability is a complex skill with involvement of many different domains, which need further research.